Analysis of the Use of Audio Visual Media in Learning Islamic Culture History in Boarding School - Ahlan, Muhammad; Zuhri, Muhammad; Razi, Fakhrul; Rochman, Achyar (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Media in learning plays a role in increasing learning motivation and making it easier to understand learning material. Learners and teachers can use and choose appropriate media for the smooth running of learning activities, among the media that can be used is audio-visual media. The purpose of this study was to analyze the use of audio-visual media in learning Islamic Culture History in Islamic Boarding Schools. This research uses a qualitative method with a descriptive approach. Data sources were taken from nine respondents consisting of Islamic Culture History teachers, boarding school leaders, and grade XI students at the boarding school. The data obtained were analyzed in three stages, (i) data were selected in accordance with the research objectives, (ii) presented in the form of narratives and tables, and (iii) concluded by linking the results of this study with previous research to obtain research findings. The results of the study found that the use of audio-visual media in learning Islamic Cultural History in Islamic Boarding Schools runs effectively and can increase student learning motivation in learning. The videos used are short in duration so that they do not exceed the scheduled learning time limit. The use of media is supported by learning facilities such as laptops, InFocus, and speakers, as well as the teacher's proficiency in operating them. The implications of using audio-visual media can arouse students' enthusiasm and motivation to learn Islamic Cultural History so that learning outcomes can be improved.